Cloning, expression, purification, crystallization and preliminary X-ray diffraction analysis of AHP2, a signal transmitter protein from Arabidopsis thaliana - Degtjarik, Oksana; Dopitova, Radka; Puehringer, Sandra; Nejedla, Eliska; Kuty, Michal; Weiss, Manfred S; Hejatko, Jan; Janda, Lubomir; Kuta Smatanova, Ivana (Acta crystallographica. Section F, Structural biology and crystallization communications, 2013)
Histidine-containing phosphotransfer proteins from Arabidopsis thaliana (AHP1-5) act as intermediates between sensor histidine kinases and response regulators in a signalling system called multi-step phosphorelay (MSP). AHP proteins mediate and potentially integrate various MSP-based signalling pathways (e.g. cytokinin or osmosensing). However, structural information about AHP proteins and their importance in MSP signalling is still lacking. To obtain a deeper insight into the structural basis of AHP-mediated signal transduction, the three-dimensional structure of AHP2 was determined. The AHP2 coding sequence was cloned into pRSET B expression vector, enabling production of AHP2 fused to an N-terminal His tag. AHP2 was expressed in soluble form in Escherichia coli strain BL21 (DE3) pLysS and then purified to homogeneity using metal chelate affinity chromatography and anion-exchange chromatography under reducing conditions. Successful crystallization in a buffer which was optimized for thermal stability yielded crystals that diffracted to 2.5 Å resolution.
Keywords: elektroforéza v polyakrylamidovém gelu; signální transdukce; Arabidopsis thaliana; Phosphotransferases; krystalizace; Transition Temperature; AHP2; X-Ray Diffraction; Signal Transduction; Arabidopsis Proteins; multi-step phosphorelay; proteiny huseníčku; Electrophoresis, Polyacrylamide Gel; Crystallization; histidine phosphotransfer proteins; fosfotransferasy; difrakce rentgenového záření; Arabidopsis; tranzitní teplota